2015
DOI: 10.1007/s12020-015-0530-0
|View full text |Cite
|
Sign up to set email alerts
|

Severe growth hormone deficiency and empty sella in obesity: a cross-sectional study

Abstract: Obesity is associated with blunted growth hormone (GH) secretion. In some individuals, hypothalamic-pituitary (HP) structural lesions may contribute to GH deficiency (GHD). We explored pituitary morphology in obese patients with suspected GHD and its association with cardiovascular risk factors, body composition, and cardiac morphology. One hundred and eighty-four adults obese patients with symptoms and signs of GHD (147 females and 37 males; mean age 46.31 ± 12.11 years), out of 906 consecutive white obese ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 42 publications
(55 reference statements)
3
24
2
Order By: Relevance
“…Obesity is correlated with blunted GH secretion (Lubrano et al 2015). It has been proposed that in some patients with AGHD, a hypothalamic-pituitary structural lesion may contribute to GH deficiency (Lubrano et al 2015).…”
Section: Growth Hormonementioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is correlated with blunted GH secretion (Lubrano et al 2015). It has been proposed that in some patients with AGHD, a hypothalamic-pituitary structural lesion may contribute to GH deficiency (Lubrano et al 2015).…”
Section: Growth Hormonementioning
confidence: 99%
“…It has been proposed that in some patients with AGHD, a hypothalamic-pituitary structural lesion may contribute to GH deficiency (Lubrano et al 2015). The close relationship between empty sella (observed frequently in obese individuals) and GH secretory capacity indicates the possibility of AGHD being natural state in obese humans (Lubrano et al 2015).…”
Section: Growth Hormonementioning
confidence: 99%
“…Blood pressure (BP), especially systolic BP (SBP), was reported to be higher in AGHD patients than in normal controls 9,10 . However, these data were obtained from heterogeneous cohorts of adult patients with GHD of varying etiologies and durations.…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH) and insulin- like growth factor 1 (IGF- 1) exert significant effects on body composition, and lipid and glucose homeostasis [ 10 ]. A wealth of studies reported that in obese subjects GH secretion is blunted [ 10 12 ], and GH and IGF- 1 have been proven to be involved in fatty infiltration of the liver [ 13 , 14 ]. Likewise, ectopic fat deposition seems to be linked to reduced GH levels [ 10 , 15 ], as well as impairment in GH production occurring with aging is one of the causes of the changes in body compartments leading to both excess adiposity and sarcopenia [ 16 ].…”
Section: Introductionmentioning
confidence: 99%